2017
DOI: 10.1111/1365-2745.12783
|View full text |Cite
|
Sign up to set email alerts
|

Below‐ground connections underlying above‐ground food production: a framework for optimising ecological connections in the rhizosphere

Abstract: Summary1. Healthy soils that contain an active microbiome and food web are critical to sustainably produce food for a growing global human population. Many studies have focussed on the role of microbial species diversity and the presence of key functional groups as important controls on the many functions that a sustainable food system relies on. 2. Here, we synthesise recent ecological empirical evidence and theory to propose that the interactions between organisms in the soil food web are the critical determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
102
2
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 202 publications
(119 citation statements)
references
References 94 publications
1
102
2
4
Order By: Relevance
“…In contrast to most studies, where rhizosphere diversity is actually lower than in bulk soil (reviewed in Berendsen, Pieterse, & Bakker, ; de Vries & Wallenstein, ), presumably due to the ability of only a small number of microbes to successfully compete in rhizosphere conditions (Hartmann et al., ), we found significantly greater bacterial diversity in soil associated with plant roots. We suggest this difference may be due to the fact that the bulk soil environment in those studies, predominantly in terrestrial ecosystems, is relatively benign as compared to that in the harsh intertidal.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast to most studies, where rhizosphere diversity is actually lower than in bulk soil (reviewed in Berendsen, Pieterse, & Bakker, ; de Vries & Wallenstein, ), presumably due to the ability of only a small number of microbes to successfully compete in rhizosphere conditions (Hartmann et al., ), we found significantly greater bacterial diversity in soil associated with plant roots. We suggest this difference may be due to the fact that the bulk soil environment in those studies, predominantly in terrestrial ecosystems, is relatively benign as compared to that in the harsh intertidal.…”
Section: Discussioncontrasting
confidence: 99%
“…In contrast to most studies, where rhizosphere diversity is actually lower than in bulk soil (reviewed in Berendsen, Pieterse, & Bakker, 2012;de Vries & Wallenstein, 2017), presumably due to the ability of only a small number of microbes to successfully compete in rhizosphere conditions (Hartmann et al, 2009), we found significantly greater bacterial diversity in soil associated with plant roots.…”
Section: Rhizosphere Influences On Microbial Communities Have Beencontrasting
confidence: 99%
“…The diversity of organisms associated with plant roots is enormous, and, as argued by De Vries & Wallenstein (), ecological interactions between plant roots and microbial and faunal networks are critical determinants of soil function and plant health. But they go a step further.…”
Section: Plant–soil (Below‐ground) Interactionsmentioning
confidence: 99%
“…Agronomic practices, such as tillage, irrigation and other inputs (e.g. pesticides, fertilizer), influence the below-ground diversity and function of soil microbes (Vries & Wallenstein, 2017), however, it is less clear if crops themselves cultivate different below-ground interactions compared to their wild relatives. Crops have reduced genetic diversity, which could influence the type, strength or diversity of interactions experienced belowground (Pérez-Jaramillo et al, 2016), and differences in root architecture (Schmidt, Bowles, & Gaudin, 2016) and root exudates (Iannucci, Fragasso, Beleggia, Nigro, & Papa, 2017) among crops and wild relatives can be pronounced.…”
Section: Introductionmentioning
confidence: 99%